دراسة وتنبوء درجة حرارة غاز الأسطوانة في محرك ديزل ذو حقن مباشر - حسن عبد الوهاب; حيدر قاسم علوان; حقي أسماعيل كاطع (Journal of Engineering and Sustainable Development, 2011)
The research aims to study the engine performance by using the pressure-crank angle diagramat differentengine speed for different fuel injection period in Direct injection diesel engine type (PETTER PHW). The present work also includes the calculating of the gas temperature of cylinder and other variables to determine the Optimum performance of the engine. Thepresent work also study the effect of several variablesi.e the effect of engine speed , fuel injection period , and the use of several models on the value of the cylinder gas temperature. The study showed at the speed (N = 1600 rpm) the engine performance can be optimized. The Ignition delay period increases with increasing engine speed. The results demonstrated that the Ignition delay period increases with the advance injection fuel angle. When using different models results showed that there are effectiveness on cylinder gas temperature curves between the first model (Single zone), and the other two ( Two zone, Multi zone).